The Impact of Affective and Normative Commitments on Work Discipline of Education Services in Labuhan Batu District - Siti Aisyah; Junita Lubis; Rizki Syahputra (Budapest International Research and Critics University, 2022)
Human resources (HR) is the backbone in running the operational activities of a company. Efforts to develop this goal can be done through affective and normative commitments so that employee work discipline continues to increase. This type of research is quantitative, and the place of this research is the Education Office of Labuhan Batu Regency. Data collection techniques used in the study were observation, documentation and questionnaires using a Likert scale. The population in this study were 95 employees of the Labuhan Batu District Education Office. The sampling technique used is saturated sampling. Since the number of employees of the Labuhan Batu Regency Education Office is 95 people (less than 100 people), all employees are taken as objects of research. The analysis used in this research is multiple linear regression. The results of the regression analysis obtained the t arithmetic value of 2.089 > t table 1.6615. This means that the affective commitment variable (X1) has a positive effect on the work discipline variable (Y). Then the significant value is 0.040 <0.05, which means that the affective commitment variable (X1) has a significant effect on the work discipline variable (Y). Based on the results of the regression analysis, the t-count value of 11.074 > t table 1.6615 means that the normative commitment variable (X2) has a positive effect on the work discipline variable (Y). Then the significant value is 0.000 <0.05, which means that the normative commitment variable (X2) has a significant effect on the work discipline variable (Y). The value of Fcount is 97.252> Ftable 3.09 with a significance value of 0.000 <0.05 affective commitment (X1) and normative commitment(X2)simultaneously has a positive and significant effect on work discipline (Y).